(untitled) (Revista de Ensino em Artes, Moda e Design, 2023)
In recent years, trend bureaus and consulting companies in the fashion industry have increasingly supported an intra and post-pandemic trend focusing on localism: turning businesses more and more towards the community. This paper aims to analyze the profile of authorial fashion brands from Ceará, in the northeast of Brazil, searching in their communication strategies on Instagram, for the use of elements of local culture, making reference to the community in which they are inserted and that actively represent the city of Fortaleza, capital of the state. The brands researched in the corpus are: Ahazando, BABA and Parko and said research was carried between March 2020 and April 2022. Beyond bibliographical analysis, categorical Content Analysis, as suggested by Lycarião (2021), was the methodology chosen to guide the analyzes in the field of traditional linguistics and hermeneutics. We intend to theorize in the present work about localism as a growing trend, the symbolism of fashion consumption, particularly in Brazil and about the importance of using elements of local culture as a marketing tool, through the interpretation of the positioning of the researched brands and their communication on Instagram.